Current Management of Intracranial Germ Cell Tumours. Issue 4 (April 2018) - Bowzyk Al-Naeeb, A.; Murray, M.; Horan, G.; Harris, F.; Kortmann, R.-D.; Nicholson, J.; Ajithkumar, T.
Abstract: Intracranial germ cell tumours (icGCTs) are uncommon tumours occurring in children and young adults. They are usually segregated into germinomas and non-germinomatous tumours (NGGCTs) in most classifications. Germinomas are highly curable tumours with multimodality treatment, but NGGCTs are associated with poorer survival outcomes. There are some differences in the approach to the management of icGCTs globally. Current research generally focuses on reducing treatment intensity, particularly the dose and volume of radiotherapy, in order to minimise the risks of late sequelae while maintaining high cure rates in icGCTs.